2002
DOI: 10.1029/2001jd000623
|View full text |Cite
|
Sign up to set email alerts
|

Energy and water dynamics of a central Amazonian rain forest

Abstract: [1] This paper presents measurements of the energy and water budgets of a tropical rain forest near Manaus, Brazil, in central Amazonia, collected between September 1995 and August 1996. Fluxes of sensible and latent heat were measured using a three-dimensional eddy covariance system mounted above the forest canopy. Using a new approach to analysis of eddy covariance data, we found that the measured fluxes increased significantly when turbulent transport on timescales of 1 to 4 hours was taken into account. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
187
6
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(233 citation statements)
references
References 36 publications
26
187
6
12
Order By: Relevance
“…Although deep convective clouds have a strong influence on surface shortwave radiation when present, their aggregate impact is limited by a lower frequency of occurrence compared to shallow cumulus. Longwave CRE is typically a factor of 5-6 smaller than SW CRE (e.g., Culf et al, 1998;Malhi et al, 2002;Burleyson et al, 2015). This study will limit most interpretation to SW CRE.…”
Section: Comparison Of Cloud Observations With Satellite: Shallow Cummentioning
confidence: 99%
“…Although deep convective clouds have a strong influence on surface shortwave radiation when present, their aggregate impact is limited by a lower frequency of occurrence compared to shallow cumulus. Longwave CRE is typically a factor of 5-6 smaller than SW CRE (e.g., Culf et al, 1998;Malhi et al, 2002;Burleyson et al, 2015). This study will limit most interpretation to SW CRE.…”
Section: Comparison Of Cloud Observations With Satellite: Shallow Cummentioning
confidence: 99%
“…net primary productivity; NPP) was assumed to be in steady state and the associated entropy change was not included in our analysis. This was a reasonable assumption, as the energy converted into biomass is only a tiny fraction (less than 1%) of the total energy flux (Malhi et al 2002).…”
Section: (D) Entropy Of Sensible and Latent Heat Flowsmentioning
confidence: 99%
“…Results from the Anglo-Brazilian Amazonian Climate Observation Study (ABRACOS; Gash et al 1996) and the more recent Large-Scale Biosphere-Atmosphere Experiment in Amazonia (LBA) (LBA 1996, Avissar et al 2002, Keller et al 2004 have provided a better understanding of the controls of forest E T at seasonal and interannual time scales. These studies have shown not only a higher E T in the dry season than in the wet season but also a higher E T over areas with less rainfall during the dry season in eastern and central Amazonia (Shuttleworth 1988, Nepstad et al 1994, Malhi et al 2002, Sommer et al 2002 well under heavy aerosol and biomass burning conditions, which are frequent in the region (Miura et al 1998). The aim of this work was to develop an empirical approach for the estimation of E T based on the vegetation condition inferred from the EVI and surface net radiation from the International Satellite Cloud Climatology Project (ISCCP; Zhang et al 1995Zhang et al , 2004).…”
Section: Introductionmentioning
confidence: 99%